Growth Characteristics of Long-Nosed Skate Dipturus oxyrinchus (Linnaeus, 1758) Inhabiting the Northeastern Mediterranean Sea - Basusta, Nuri; Ozel, Fatih Volkan (Mdpi, 2022)
Simple Summary Skates and rays generally have low fecundity, delayed maturation age and slow growth rates. These life history traits make them very vulnerable to commercial fisheries' activities, although they are not usually target species. Understanding age and growth is important for stock assessment of the long-nose skate. We believe that determining these can be the first step toward correct management actions. Little is known about the growth characteristics of the long-nose skate in the Northeastern Mediterranean Sea. Our study aimed at comparing three different growth models (the von Bertalanffy, the Robertson (logistic), and Gompertz) and also the absolute and relative growth characteristics of this species. Our results show that the relationship between the age of the long-nose skate and its total length is adequately explained by the Robertson (logistic) growth model, with the Gompertz growth model being the second best. This study aims to determine the age and growth characteristics of Dipturus oxyrinchus living in the Northeastern Mediterranean Sea and to present data that can provide a comparison with previous studies on the same subject. A total of 255 long-nose skates at a total length of 12.2-93.5 cm and weight of 8.34-3828 g were collected as non-target species from a commercial fishing boat. The male-female ratio was determined as 1:1.27. Using the von Bertalanffy equation and the Gompertz or logistic growth models, the growth parameters of Dipturus oxyrinchus were estimated as L infinity = 154.0, K = 0.064, t(0) = -1.622; L infinity = 104.0, K = 0.35, I = 4.99; L infinity = 128.40, K = 0.19, I = 4.39 for all individuals, respectively. Maximum absolute growth was calculated as 9.33 cm at 5-6 years of age. Maximum relative growth at 1-2 years of age was estimated as 36.39%. Both absolute and relative growth were minimal in the 11-12 age group. The highest condition factor value was estimated as 0.416 in the 8-year-old group. As a result, the growth data of long-nose skates were obtained for the first time in the Northeastern Mediterranean Sea.
Keywords: age; growth; Dipturus oxyrinchus; long-nosed skate; Northeastern Mediterranean Sea